Evaluation Of The Safety Of Visitors To The Umbul Besuki Tour In Ponggok Village In Terms Of The Construction Of Facilities And Infrastructure - Dody Irnawan; Rizqiyah Safitri Juwito (Talenta Publisher, 2021)
Tourism cannot be separated from human life, because it is closely related to social and economic activities that can be enjoyed and is a way for humans to socialize. The city of Klaten is known to have many potential objects and tourist attractions that are able to attract tourists. This is what is then captured by tourism business actors to create new tourist objects and attractions that contain educational, creative, and attractive messages by taking the concept of nature. Umbul Besuki is a water recreation park in Ponggok Village Tourism, precisely in Kringan-Ponggok Hamlet. This area was developed as an unspoiled green area typical of a rural atmosphere. There were some visitors who were worried when swimming in the pool, for example slipping on the stairs, drowning because there was no sign of the depth of the pool, and falling from a temporary rest area. The importance of a material selection in planning a tourist attraction and complete safety support facilities, this is because many visitors of various ages. from the analysis and monitoring results, there are still many technical provisions that have not been considered, with the conclusion of the architectural design design